Tanggung Gugat Wanprestasi atas Jual Beli Tanah dan Bangunan di Bawah Tangan (Studi Putusan No. 1593 K/Pdt/2016) - Annisa Setiadi; Lady Dara Krismasi; Renani Oktavia; Yuliatin Nur Ningsih (Faculty of Law Hang Tuah University, 2021)
Efforts to obtain land can be carried out in various ways, one of which is a sale and purchase agreement that must be carried out at a place designated by the Land Deed Making Officer (PPAT). There is not much buying in the sale and purchase of land and buildings made under the hands without going through PPAT, so the selling party cannot fulfill his wishes due to negligence or deliberation (default). The legal consequences of default can be in the form of payment of compensation, replacement or coverage through a judge, payment of compensation for the debtor, payment of case fees before the judge, and agreement that can be done or shared with the help of changing compensation.